Effect of Molasses Based Multi-nutrient Supplement Containing Chromium on Nutrient Utilization, Milk Yield, Microbial Protein Flow and Antioxidant Status of Lactating Murrah Buffaloes - Patil, Ashok Kumar; Verma, A K; Singh, Putan; Das, Asit (Indian Journal of Animal Nutrition, 2019)
This experiment was conducted to study the effect of supplement Molasses based multi-nutrients containing chromium Picolinate on nutrient utilization, milk yield, microbial protein flow and antioxidant status of lactating Murrah buffaloes. Thus 21 lactating buffaloes were equally divided into three groups (n=7) on the basis of body weight and milk yield. Basal diet consisting wheat straw, maize green and concentrate mixture were fed to all groups. In addition to basal diet, the animals of group T2 fed 250 g Molasses based multi-nutrients supplement (MMS-1) and group T3 fed with 250 g MMS plus 5 mg Chromium Picolinate (MMS-2) . The digestibilities of the nutrients remained uninfluenced (P>0.05) among all the groups. Dietary MMS supplementation tended to improvement in milk yield by 18 (T2) and 16 (T3)Â Â  percent. The activities of superoxide dismutase, catalase and glutathione peroxidase were significantly (P